Structural performance evaluation for prototype walls built with EVA blocks - Melo, Aluísio Braz (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2009)
The utilization of EVA (Ethylene Vinyl Acetate) waste, a byproduct from the production of sandals, in construction projects has been the object of research in the last 10 years. It is known that EVA waste has great potential to be used as lightweight aggregate, replacing natural aggregates in the production of alternative cement composites. As well as highlighting the development of research into the application of these composites in the production of light blocks, this study shows an important stage in the process of evaluation of the structural performance of the proposed precast. The evaluation of occupancy loads and impacts on the prototype walls built with EVA blocks was done through tests (impacts of soft and hard materials, repercussions of abrupt closing of doors and loads coming from suspended pieces) in order to simulate accidental and normal situations in building use. In the construction proce ss of the prototype, the EVA blocks proved to be easy to use in ways that are important to help reducing construction and demolition waste. According to the current knowledge, based on previous studies and considering the positive performance of the prototype as shown by the tests, 1.2 MPa is suggested as an acceptable parameter of compressive strength for the EVA block.